Magneto-thermal limitations in superconducting cavities at high radio-frequency fields - Parajuli, I.; Ciovati, G.; Gurevich, A. (Frontiers in Electronic Materials, 2024)
The performance of superconducting radio-frequency Nb cavities at high radio-frequency (rf) fields in the absence of field emission can be limited by either a sharp decrease of the quality factor Q0(Bp) above peak surface magnetic fields Bp ∼100 mT or by a quench. We have measured Q0(Bp) at 2 K of several 1.3 GHz single-cell Nb cavities with different grain sizes, and with different ambient magnetic fields and cooldown rates below the critical temperature. Temperature mapping and a novel magnetic field mapping systems were used to find the location of ”hot-spots” and regions of trapped magnetic flux. The use of a variable input coupler allowed further exploring the dissipative state. The results showed a remarkable thermal stability in some cavities with up to 200 W of rf power dissipation at 2 K, whereas other cavities quenched at much lower rf power. We observed a narrow distributions of the onset fields of hot-spots which were not affected by thermal cycling or by conditions which favor the formation of Nb hydrides. Furthermore, a poor correlation was found between the location of hot-spots and trapped vortices. We suggest that the totality of our experimental data can be explained by a sharp increase of the residual surface resistance above 120-140 mT due to the field-induced breakdown of a proximity-coupled metallic suboxide layer at the surface.